A Signal Reconstruction Method Based on Quadratic Spline Interpolation Applied in Power Quality Analysis for SCM-TTU - Deng, Siyang; Liu, Zhu; Huang, Lvchao (Journal of physics. Conference series, 2020)
Aiming at the accurate and quick analysis of power quality especially of harmonic problem in power system, interpolation approaches should be applied if the samples collected by hardware are not matched with Fast Fourier Transform (FFT) calculation. A quadratic spline interpolation algorithm is proposed on Single Chip Micyoco-Transformer Terminal Unit (SCM-TTU) in this paper. This algorithm considers the continuous of interpolation function and also the first derivative in order to improve the accuracy. It could be applied before FFT calculation to avoid the mismatch of sampling rates. A simulation with mathematic example and also an application with SCM-TTU contains the harmonics from 2nd to 50th orders are experimented, results are presented to show the effectiveness.